2016
DOI: 10.1038/srep38330
|View full text |Cite
|
Sign up to set email alerts
|

DETC-based bacterial cellulose bio-curatives for topical treatment of cutaneous leishmaniasis

Abstract: The treatment of leishmaniasis still relies on drugs with potentially serious adverse effects. Herein, we tested a topical formulation of bacterial cellulose (BC) membranes containing Diethyldithiocarbamate (DETC), a superoxide dismutase 1 inhibitor. Leishmania-infected macrophages exposed to BC-DETC resulted in parasite killing, without pronounced toxic effects to host cells. This outcome was associated with lower SOD1 activity and higher production of superoxide and cytokine mediators. Topical application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Infected neutrophil cultures treated with heme displayed substantial increase in both MPO (Figure 5 A) and NE (Figure 5 B) activity whereas treatment with iron failed to induce such effects. It has been shown that the induction of superoxide dismutase 1 (SOD-1) favors Leishmania persistence ( 29 ), and that SOD-1 inhibition leads to enhanced parasite killing by human macrophages ( 30 ). In the present study, we observed that incubation of the infected neutrophil cultures with either heme or Fe +2 resulted in additional increases in SOD-1 activity compared with untreated infected cultures (Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…Infected neutrophil cultures treated with heme displayed substantial increase in both MPO (Figure 5 A) and NE (Figure 5 B) activity whereas treatment with iron failed to induce such effects. It has been shown that the induction of superoxide dismutase 1 (SOD-1) favors Leishmania persistence ( 29 ), and that SOD-1 inhibition leads to enhanced parasite killing by human macrophages ( 30 ). In the present study, we observed that incubation of the infected neutrophil cultures with either heme or Fe +2 resulted in additional increases in SOD-1 activity compared with untreated infected cultures (Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…We build on these currently available tools by developing a dual reporterexpressing L. braziliensis. Besides the advantage of having two stable reporters, this line was developed upon a field isolate (de Moura et al, 2005) that has been widely employed in a variety of studies addressing the pathogenesis of CL caused by L. braziliensis (Novais et al, 2013(Novais et al, , 2017, in addition to drug (Santos et al, 2014;Celes et al, 2016) and vaccine development (Salay et al, 2007;Thalhofer et al, 2011;Carneiro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Monolayers received 3 × 10 6 L. braziliensis promastigotes and were incubated at 35 °C in supplemented DMEM medium for 24 h. Infected macrophages were washed to remove non-internalized parasites. Cultures were treated with Diethyldithiocarbamate (DETC) (1 or 2 mM) (Khouri et al, 2010; Celes et al, 2016), Hydrogen Peroxide (100 or 150 μM), N-acetyl cysteine (NAC) (1, 5, or 10 mM), Apocynin (APO) (20 mM) (Paiva et al, 2012), Tempol (4-Hydroxy-TEMPO) (0.5, 1, or 5 mM) (Hahn et al, 1997; Shilo and Tirosh, 2003; Kim et al, 2017) and Menadione (1, 10, or 20 μM) (Mittra et al, 2013), all from SIGMA. Compounds were diluted in DMSO (vehicle).…”
Section: Methodsmentioning
confidence: 99%
“…The SOD1-inhibitor diethyldithiocarbamate (DETC) kills intracellular parasites in vitro and in vivo in a murine model of cutaneous leishmaniasis (Khouri et al, 2010). We have previously shown that DETC can be used as a topical treatment in the cutaneous lesions caused by L. braziliensis (Celes et al, 2016), suggesting that manipulation of the redox status during in vitro infection with L. braziliensis can contribute to the identification of novel therapeutic alternatives. To this purpose, we incubated promastigotes and infected macrophages with Glutahtione replenisher N-acetyl-cysteine (NAC) (Aldini et al, 2018), SOD-mimetic Tempol (Wilcox, 2010) and O2- -generator menadione (Hassan, 2013).…”
Section: Introductionmentioning
confidence: 99%